Managing Environmentally Sustainable Innovation : Insights from the Construction Industry. - Bossink, Bart (Taylor & Francis, 2011)
This volume provides a management concept for sustainable innovation management in commercial and governmental organizations. It provides answers to the question how people, teams, projects, companies and governments can shape the innovation process towards sustainability while maintaining or improving a profitable financial performance.